Development of the parliamentary parties’ institute in modern Russia: prospects and trends - S. S. Stepanova (Управление)
The article analyzes the current state of the institution of parliamentary parties in the Russian Federation, the political and legal conditions of their activities, and examines the political processes that determine the trends and prospects for their development. The study of modern scientific literature on the relevant topic made it possible to get acquainted with various assessments of the state of the parliamentary parties institution in Russia, as well as with the factors that determine the features of their development at the present time. The method of problem-chronological analysis made it possible to determine the main stages in the evolution of parliamentary political parties in Russia. The method of comparative analysis made it possible to identify common and specific features of their development in current conditions. The development of the institution of parliamentary parties is considered in the context of the modernization processes of the entire political system of Russian society, the evolution of the public administration system. The author notes the significant role of external factors, including crisis phenomena in the international situation, growing tensions and the transition to open confrontation between Russia and the West. This has a considerable impact on the ideological component of political parties, both pro-government and those representing the parliamentary opposition. The article concludes that the changes taking place in the socio-political life of modern Russia predetermine the emergence of new forms and mechanisms of decision-making, affect the role of parliament and parliamentary parties in the process of political decision-making, affect the capabilities and potential of political parties. According to the author, the prospects for the development of the institution of parliamentary parties in modern Russia directly depend on the entire system of public administration and social development, their improvement and further enhancement of the role of political parties at the national, regional and local levels.